A prospective study of the influence of perceived coaching style on burnout propensity in high level young athletes: using a self-determination theory perspective - Isoard-Gautheur, S.; Guillet-Descas, E.; Lemyre, N. (The Sport Psychologist, 2012)
The article presents sports psychology research on the coach-athlete relationship for high school athletes at a training center for elite athlete athletes who participate in international competition. Structural equation modeling of results of interview with athletes is used to examine the influence of the athletes' perceptions of coaching behaviors on their tendency to experience burnout while training. Coaching style was found to significant relate to the athletes' psychological needs, particularly autonomy. Implications of the study for coaching techniques are discussed.